ECOWAS AND THE CHALLENGES OF REGIONAL INTEGRATION: AN ASSESSMENT OF NIGERIA'S HEGEMONIC ROLE - Owoeye , Gbenga; Ayodeji , Oluwatobi (International Journal of Political Science and International Relations (IJPSIR), 2025)
Recently, the Economic Community of West African States (ECOWAS) lost three of its founding members, which had devastating implications for the effective performance of the regional institution. The efforts of Nigeria, a major player in the regiony, to strengthen and provide direction have not yielded the desired results, as the influence of the regional body continues to diminish. Therefore, this study examined Nigeria’s role in mitigating the contemporary challenges facing the regional body. The study elicited data from existing sources to better understand the problems. The study found that the lack of a central authority to enforce rules and regulations has hindered the effectiveness of the regional body. Study findings also show that external interference in the politics of the region has weakened the effectiveness of the body. Furthermore, results revealed that Nigeria’s domestic challenges have worsened the problems of the regional international institution